Synthesis of Allene-Containing Apocarotenoids by Cross-Coupling Strategy - Sakaguchi, Kazuhiko; Nishioka, Yuto; Kinashi, Naoto; Yukihira, Nao; Shinada, Tetsuro; Nishimura, Takahiro; Hashimoto, Hideki; Katsumura, Shigeo (Synthesis, 2020)
The stereocontrolled total synthesis of the allene and carbonyl conjugated apocarotenoids, paracentrone and 19-hexanoyloxyparacentrone 3-acetate, was achieved by sequential cross-coupling reactions using boronic acid ester and iodine- or tin-substituted C5 dienes, which were the building blocks for the elongation of the conjugated polyene systems at both terminals.
Keywords: apocarotenoid; paracentrone; fucoxanthin; cross-coupling; C5 diene; allene